Protective mechanism of Coprinus comatus polysaccharide on acute alcoholic liver injury in mice, the metabolomics and gut microbiota investigation - Jinyan Yu; Jianguang Sun; Min Sun; Weidong Li; Dongmei Qi; Yongqing Zhang; Chunchao Han (Food Science and Human Wellness)
Coprinus comatus polysaccharide (CCP) has significant hepatoprotective effect. To explore hepatoprotective mechanism of CCP, the study analyzed preventive effect of CCP on acute alcoholic liver injury in mice by histopathological examination and biochemical analysis. Simultaneously, hepatoprotective mechanism was also analyzed in conjunction with metabolomics and proliferation of gut microbiota. The results showed that CCP significantly decreased alanine aminotransferase (ALT), aspartate aminotransferase (AST) and triglyceride (TG) levels in serum of alcoholic liver disease (ALD) mice. Histopathological examination showed that CCP can significantly improve liver damage. Metabolomics results showed that there were significant differences in the level of metabolites in liver tissue of control group, ALD group and CCP group, including taurine, xanthosine, fumaric acid and arachidonic acid, among others. Metabolites pathways analysis showed that hepatoprotective effect of CCP was related to energy metabolism, biosynthesis of unsaturated fatty acids, amino acids metabolism and lipid metabolism. Additionally, CCP inhibited an increase in the number of Clostridium perfringens, Enterobacteriaceae and Enterococcus, and a decrease in the number of Lactobacillus and Bifidobacterium in the gut of ALD mice. All these findings suggested that CCP treatment reversed the phenotype of ethanol-induced liver injury and the associated metabolites pathways.